2015
DOI: 10.1136/oemed-2014-102548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial sleep restriction and subsequent daytime napping on prolonged exertional heat strain

Abstract: These results suggest that PSR augments physiological and psychological strain and reduces vigilance in the heat. Taking a nap seemed to be effective in reducing psychological strain and inhibiting the decrease in vigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
(28 reference statements)
2
24
1
Order By: Relevance
“…This interesting finding indicates that the effect of PSR on thermal strain during exercise-heat-stress may be dependent on the time of day and provides supporting evidence, in a controlled laboratory setting, for the field observation that sleep disruption is often a risk factor for exertional heat illness 3. Unfortunately, we do not concur with the contention of Tokizawa et al 1 that daytime napping can ‘handle the safety risk’ for heatstroke in the afternoon after PSR. A closer inspection of the data in figure 3 shows that a nap results in participants underestimating thermal sensation and fatigue (physical and psychological) during subsequent exercise-heat-stress.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…This interesting finding indicates that the effect of PSR on thermal strain during exercise-heat-stress may be dependent on the time of day and provides supporting evidence, in a controlled laboratory setting, for the field observation that sleep disruption is often a risk factor for exertional heat illness 3. Unfortunately, we do not concur with the contention of Tokizawa et al 1 that daytime napping can ‘handle the safety risk’ for heatstroke in the afternoon after PSR. A closer inspection of the data in figure 3 shows that a nap results in participants underestimating thermal sensation and fatigue (physical and psychological) during subsequent exercise-heat-stress.…”
contrasting
confidence: 99%
“…We were very interested to read the recent article by Tokizawa et al 1 that investigated the effect of partial sleep restriction (PSR) and a daytime nap on thermal strain during exercise heat stress. Tokizawa et al confirm our previous findings2 that disrupted sleep does not affect thermal strain during exercise-heat-stress in the morning but extend our findings by showing that PSR increases heat strain during moderate exercise-heat-stress in the afternoon (core temperature <37.8°C and heart rate <110 bpm).…”
mentioning
confidence: 99%
“…Access to air conditioning during sleeping hours in hot humid regions , can significantly influence individuals ’ sleep quality, including among farmworkers (7,77); however, information about presence or absence of air conditioning in farmworker housing was not collected. Furthermore, individuals whose have inadequate sleep and physically exert themselves in a hot environment have reduced behavioral alertness (78). Farmworkers with poor sleep quality who are exposed to high temperatures at work may therefore have an elevated risk of hurting themselves on the job .…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the opportunity to respond to the letter by Professor Walsh and colleagues,1 regarding our article, ‘Effects of partial sleep restriction and subsequent daytime napping on prolonged exertional heat strain’ 2. They suggested that daytime napping following partial sleep restriction might increase the risk of exertional heat-related illness because the participants who took a nap felt ‘less hot’ and ‘less fatigued’ than if they had not taken a nap.…”
mentioning
confidence: 99%